No detectable role for predators mediating effects of aquatic habitat size and permanence on populations and communities of container‐dwelling mosquitoes. (6th April 2017) - WESTBY, KATIE M.; JULIANO, STEVEN A.
Abstract : 1. General theory from aquatic ecology predicts that smaller aquatic habitats have shorter hydroperiods favouring species that are better resource competitors and complete development quickly. Larger habitats are predicted to have longer hydroperiods enabling longer‐lived predators to persist. Habitats with long hydroperiods and predators are predicted to favour slower‐developing, predator‐resistant species, rather than competitive species. 2. In a field experiment, habitat size and hydroperiod were manipulated independently in water‐filled containers, to test these hypotheses about processes structuring aquatic communities. Human‐made containers were used that are dominated by mosquitoes that vary in desiccation resistance, competitive ability, and predation resistance. 3. Habitat size and drying had significant effects on abundances of larvae of the common species in these communities. There was sorting of species by habitat size and by drying, with species that are better competitors relatively more abundant in smaller, more ephemeral habitats, and predator‐resistant, slower‐developing species relatively more abundant in larger or permanently flooded habitats. There were no detectable effects of habitat size or drying on the dominant predator. 4. Habitat size and its interaction with drying affected inputs of eggs to containers. Habitat size also affected relative abundances of the two dominant species in the egg population. 5. Although habitat size and hydroperiod significantly affected composition of these communities, these impacts did not appear to be mediated through effects on predator abundance. Species‐specific differences in habitat size and drying regime preferences, and habitat‐dependent larval performance appear to be the main forces shaping these communities.